Perdagangan Islam di Era Modern - Gewatra Davina Yasa Albion; Kusuma Mukti Dewantoro; Revalina Hafizhah Salsabila; Xena Anastasya; Saifuddin Zuhri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Trade is an activity that is inherent in human life and in Islam trade has an important role in advancing the economy and facilitating the exchange of goods and services in accordance with Islamic knowledge, Sharia Law, Globalization and technological developments. Apart from that, changes in regulations are one of the challenges facing Islamic trade in the modern era. However, there are also important opportunities, such as e-commerce, Islamic finance, and halal products, that enable Muslim traders to innovate and compete in global markets. In an era of ever-changing global trade, Muslim traders around the world must continually monitor changes in consumer demand, regulations and technology. With a good understanding of the markets and a commitment to Islamic principles, traders can take advantage of Islamic trading opportunities in this modern era. Halal trade is a clear example of how adaptation to these changes can bring success in the context of Islamic trade.